(untitled) (Fiep Bulletin - online, 2013)
This study had as objective to make a correlation between the quality of life and the painful manifestations, heart rate (HR) and blood pressure (BP), before and after the labor gymnastics in a food company. In a appropriated sample composed by 39 employees was applied the Medical Outcomes Study Shorts Form - 36 (SF-36), collected painful manifestations through the analogical scale of pain, measured the heart rate (HR) and blood pressure (BP) before and after the labor gymnastics practices, understood by sessions of 30 minutes. Through the analysis statistics, it was evidenced that in relation to the clinical variables of pain intensity, heart rate and blood pressure, it was found a significant statistical difference between the values measured before and after the sessions of labor gymnastics. The workers report better quality of life in the physical and emotional aspects (83,33? 20,9 and 72,64? 28,4 respectively). The pain and vitality aspects report the worst rates among the participants (40,12 11,7 and 55,64 13,2 respectively). In all the statistical tests, it was used a level of significance of 5%. The analyses were done in statistical software SPSS (Statistical Package will be Social Sciences) version 15.0. Considering the results it was possible to detect the importance of the quality of life values measured in the SF-36 during the working journey. The correlation between the clinical measures of the workers and the eight domains of the variable quality of life reported significant between the functional capacity and the average of the pain intensity. For the better functional capacity, the lesser is the pain intensity.